2018
DOI: 10.1108/ijsms-08-2017-0082
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the regional strategies for developing and advancing the Chinese sport industry

Abstract: Purpose The purpose of this paper is to examine the key factors that affect the formulation of regional strategies for developing and advancing the sport industry in China. Design/methodology/approach Guided by the comparative advantage theory, qualitative and quantitative research procedures were carried out to analyze the variables that were deemed necessary for the development of regional advantages. Findings The findings of this study indicated the importance and relevance of understanding these compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To test content validity, we asked five sport management professors specialized in fitness operation to examine the relevance, representativeness, and clarity of each item. Based on a standard of 80% agreement among the panel members [46], we retained all of the items, although we revised numerous items for clarity. To verify concurrent validity [38,47], we examined the service quality scale using an established service-related outcome variable: satisfaction [28,48,49].…”
Section: Phase IImentioning
confidence: 99%
“…To test content validity, we asked five sport management professors specialized in fitness operation to examine the relevance, representativeness, and clarity of each item. Based on a standard of 80% agreement among the panel members [46], we retained all of the items, although we revised numerous items for clarity. To verify concurrent validity [38,47], we examined the service quality scale using an established service-related outcome variable: satisfaction [28,48,49].…”
Section: Phase IImentioning
confidence: 99%
“…Literature review and hypotheses 2.1 Perceived self-efficacy and participation in sports or exercise The literature shows that there are numerous elements that may influence people to take up physical exercise or sport and maintain the habit of regular practice (Wang et al, 2018). Among these elements are the socio-cultural environment surrounding the individual, the prevalent economic conditions, sports traditions among regions and communities and the priorities established by local authorities, as well as the degree of economic development, consumption, and local authority support for sport-related leisure in the region in question (Wang et al, 2018). It is also useful to consider the preferences that different profiles of people may present when exposed to the offer of sports centers (Haro-Gonz alez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has also demonstrated that the provision of sports facilities, equipment, and programs-or the lack thereof-can influence the decisions people on whether to practice physical exercise and/or sport or not (e.g. : Wang et al, 2018). While such external conditioning factors will result in individuals having certain options for practicing regular physical exercise and/or sport, it is equally necessary to study the internal factors specific to each person-those that are under their control-in terms of how they, too, influence the degree to which individuals adopt a regular physical exercise practice and/or a sport.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, die-hard fans are very satisfied and feel a more positive quality of service (Xiao et al, 2020). The organization of sports activities can have a positive impact in terms of economy, environment, and social, if the event organizer has managed the event effectively and efficiently in accordance with the rules and pays attention to the quality of service and audience satisfaction such as facilities, security, environmental cleanliness, on the ticket price paid (Moreno et al, 2016;Wang et al, 2018;Zhuo et al, 2020). The quality of services provided by the management of the organizers provides added value to the sports activities held (Kersulić et al, 2020).…”
Section: Introductionmentioning
confidence: 99%